Osmoregulation of the salt-tolerant yeast Debaryomyces hansenii grown in a chemostat at different salinities. - Larsson, C (1990)
The intracellular solute composition of the salt-tolerant yeast Debaryomyces hansenii was studied in glucose-limited chemostat cultures at different concentrations of NaCl (4 mM, 0.68 M, and 1.35 M). A strong positive correlation between the total intracellular polyol concentration (glycerol and arabinitol) and medium salinity was demonstrated. The intracellular polyol concentration was sufficient to balance about 75% of the osmotic pressure of the medium in cultures with 0.68 and 1.35 M NaCl. The intracellular concentration of K+ and Na+, which at low external salinity gave a considerable contribution to the intracellular water potential, was only slightly enhanced with raised medium salinity. However, the ratio of intracellular K+ to Na+ decreased; but this decrease was less drastic in the cells than in the surrounding medium, i.e., the cells were able to select for K+ in favor of Na+. The turgor pressure, which was estimated on the basis of intracellular solute concentrations, was 2,200 kPa in cultures with 4 mM NaCl and decreased when the external salinity was raised, resulting in a value of about 500 kPa in cultures with 1.35 M NaCl. The maintenance of a positive turgor pressure at high salinity was mainly due to an increased production and accumulation of glycerol.